2013
DOI: 10.1371/journal.pone.0059105
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Soft Tissues Is Promoted by MMP1 Treatment after Digit Amputation in Mice

Abstract: The ratio of matrix metalloproteinases (MMPs) to the tissue inhibitors of metalloproteinases (TIMPs) in wounded tissues strictly control the protease activity of MMPs, and therefore regulate the progress of wound closure, tissue regeneration and scar formation. Some amphibians (i.e. axolotl/newt) demonstrate complete regeneration of missing or wounded digits and even limbs; MMPs play a critical role during amphibian regeneration. Conversely, mammalian wound healing re-establishes tissue integrity, but at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 59 publications
0
40
1
Order By: Relevance
“…, ; Mu et al. ). In the current investigation, we have focused on this P2 amputation model and show that the amputation injury response is not inert but quite dynamic with bone tissue displaying a novel biphasic (degradation/new bone deposition) response that parallels the fracture healing response of the P2 element.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, ; Mu et al. ). In the current investigation, we have focused on this P2 amputation model and show that the amputation injury response is not inert but quite dynamic with bone tissue displaying a novel biphasic (degradation/new bone deposition) response that parallels the fracture healing response of the P2 element.…”
Section: Discussionmentioning
confidence: 99%
“…; Mu et al. ). In the neonate, we have shown that bone morphogenetic protein 2 (BMP‐2) induces a regenerative response in the amputated P2 bone that involves the formation of a transient blastema, the creation of an endochondral ossification center, and the patterned extension of the stump bone (Yu et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…94 Similarly, promoting degradation of the ECM by the exogenous addition of MMPs increased the recruitment of multipotent cells to the plane of amputation. 110 Hence, it is clear that the accessibility of ECM products is critical for the cell recruitment toward the formation of a blastema-like structure, although the specific ECM factors are still unidentified.…”
Section: Regulation Of Digit Tip Regenerationmentioning
confidence: 99%
“…19 Our recent study also indicated the application of MMP1 is able to accelerate murine digit regeneration with less fibrous scar, partially because of its role in anti-fibrosis. 48 These studies made MMP1 an ideal candidate in improvement of myoblast transplantation. Our current study used a retrovirus vector to transfer MMP1 gene into C2C12 myoblasts in order to extending MMP1 biological lifetime prior to cell transplantation into animals.…”
Section: Discussionmentioning
confidence: 99%